Mission in Mamuratu'l-Aziz Province: Capucins - Kilicoglu, Selim (Istanbul Univ, Research Inst Turkology, Dept Art History, 2022)
Missionary activities have been active in the Ottoman lands since the 16th century. The Anatolian geography, which is located in the Ottoman lands and defined as the Bible Land in missionary reports, is one of the important areas of mission work. Mamuratu'l-Aziz Province, which is located in the Anatolian geography today and includes the provincial borders of Elazig, is among the central stations of missionary in the 19th century. The main purpose of this study is to draw attention to the French mission in the mission works carried out in the Ottoman lands, and to the activity and working areas in Anatolia in particular, and to create a discussion area. In this study, which I have divided into three main sections, the general scheme of Missionary in the Ottoman lands consists of the position of the French in this general scheme and the location of Mamuratu'l-Aziz and Harpoot in the Anatolian geography. In the study, drawings obtained from Ottoman archive documents and images taken by the traveler or their travelers in the period were used. In this region, the Capuchins, which is affiliated with the Franciscan community, built and carried out studies at the college level under the auspices of the French State. Within the scope of the article, the construction activities carried out by the Capuchins in Harpoot and Mamuratu'l Aziz were evaluated.
Mamuratü'l-Aziz Vilayeti Yabancı Misyonu: Kapusenler (Capucins)
Keywords: Capucins; Mamuratu'l-Aziz; Harpout; France College; Anatolia